Institutional Properties of the South East European Region - Draskovic, Mimo; Grgurevic, Niksa; Delibasic, Milica (Economy of Regions, 2015)
This paper will identify and analyze the basic institutional characteristics of the region of South East Europe (SEE6), because the building of institutions is one of the main conditions for sustainable development. Basic theoretical and practical barriers, that crucially influenced the current unfavorable transitional institutional characteristics in SEE6, will be researched in a selective way. The aim of this paper is to demonstrate the essential institutional differences of this region in comparison with developed countries, particularly in terms of real institutional change, the application of institutional pluralism and the main institutional barriers. The paper starts from the hypothesis that ignoring the institutional pluralism and domination of alternative institutions in SEE6 led to dysfunctionality of institutional change, which had a negative impact on all indicators of economic development in the surveyed countries. The emphasis is on the factors of monistic anti-institutional action, from which the alternative institutions stand out for their destructive significance. It points to devastating and anti-developmental consequences of their actions, and their theoretical support of neoliberal type, which is in practice vulgarized and converted into a quasi-neoliberalism. It identifies the real and concrete causes of reproduced institutional vacuum. The findings from the study suggest that countries of the SEE6 region should apply civilization-proven development models of institutional pluralism type. This indicates the importance of taking real institutional changes and urgent overcoming the quasi-institutional forms in order to successfully valorize the economic resources in the countries of SEE6.